The Critical Role of Oxidative Stress in Sarcopenic Obesity - Vilos-Ortiz, C; Gonzalez-Rojas, A; Cabello-Verrugio, C (Hindawi Limited, 2021)
Sarcopenic obesity (SO) is a combination of obesity and sarcopenia that primarily develops in older people. Patients with SO have high fat mass, low muscle mass, low muscle strength, and low physical function. SO relates to metabolic syndrome and an increased risk of morbimortality. The prevalence of SO varies because of lacking consensus criteria regarding its definition and the methodological difficulty in diagnosing sarcopenia and obesity. SO includes systemic alterations such as insulin resistance, increased proinflammatory cytokines, age-associated hormonal changes, and decreased physical activity at pathophysiological levels. Interestingly, these alterations are influenced by oxidative stress, which is a critical factor in altering muscle function and the generation of metabolic dysfunctions. Thus, oxidative stress in SO alters muscle mass, the signaling pathways that control it, satellite cell functions, and mitochondrial and endoplasmic reticulum activities. Considering this background, our objectives in this review are to describe SO as a highly prevalent condition and look at the role of oxidative stress in SO pathophysiology. © 2021 Andrea Gonzalez et al.